Glycine Betaine and β-Aminobutyric Acid Mitigate the Detrimental Effects of Heat Stress on Chinese Cabbage (Brassica rapa L. ssp. pekinensis) Seedlings with Improved Photosynthetic Performance and Antioxidant System - Jin Quan; Weiwei Zheng; Meifang Wu; Zhuojun Shen; Jingru Tan; Zewei Li; Biao Zhu; Seung-Beom Hong; Yanting Zhao; Zhujun Zhu; Yunxiang Zang (Plants, 2022)
Heat stress is one of the major abiotic factors that limit the growth, development, and productivity of plants. Both glycine betaine (GB) and β-aminobutyric acid (BABA) have received considerable attention due to their roles in stimulating tolerance to diverse abiotic stresses. In order to understand how GB and BABA biostimulants alleviate heat stress in a cool-weather Chinese cabbage (Brassica rapa L. ssp. pekinensis) plant, we investigated the GB- and BABA-primed heat-stressed plants in terms of their morpho-physiological and biochemical traits. Priming with GB (15 mM) and BABA (0.2 mM) was conducted at the third leaf stage by applying foliar sprays daily for 5 days before 5 days of heat stress (45 °C in 16 h light/35 °C in 8 h dark) on Chinese cabbage seedlings. The results indicate that GB and BABA significantly increased chlorophyll content, and the parameters of both gas exchange and chlorophyll fluorescence, of Chinese cabbage under heat stress. Compared with the unprimed heat-stressed control, the dry weights of GB- and BABA-primed plants were significantly increased by 36.36% and 45.45%, respectively. GB and BABA priming also greatly mitigated membrane damage, as indicated by the reduction in malondialdehyde (MDA) and electrolyte leakage through the elevation of proline content, and increased activity levels of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX). Taken together, GB and BABA have great potential to enhance the thermotolerance of Chinese cabbage through higher photosynthesis performance, osmoprotection, and antioxidant enzyme activity.